2011
DOI: 10.17986/blm.2011161722
|View full text |Cite
|
Sign up to set email alerts
|

Şüpheli Ölüm Olgusunda Organ Nakli Adli Tıbbi ve Etik Sorunlar

Abstract: Gelişen tıp teknolojisi, organ nakli ile yaşama ümidi kalmayan insanlara ikinci yaşamı sunarken, beraberinde hukuk ve etik tartışmayı başlatmıştır. Bu çalışmada bir olgu nedeni ile adli olgularda yapılan organ nakillerinde karşılaşılan yasal ve etik sorunları tartışmak amaçlanmıştır. Çalışmamızda beyin ölümü gerçekleşmiş, organ nakli süreci başlatılmış ancak aynı zamanda şüpheli ölüm nedeni ile adli olgu bildirimi yapılan ve Adli makamlarca Anabilim Dalımızdan görüş istenen bir olgu ve süreç ele alınmıştır. Od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Obtaining approval of the forensic physician is easier in case of traffic accidents, gun shots and stabbing wounds, where the organs to be removed are not damaged On the other hand, transplantation process may become difficult when the cause of death cannot be determined in forensic suspicious deaths. Mustafa Demirer et al have reported that removal of organs in case of suspicious death do not negatively affect the investigations to be performed in autopsy, so that kidneys and liver may be transplanted appropriately 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining approval of the forensic physician is easier in case of traffic accidents, gun shots and stabbing wounds, where the organs to be removed are not damaged On the other hand, transplantation process may become difficult when the cause of death cannot be determined in forensic suspicious deaths. Mustafa Demirer et al have reported that removal of organs in case of suspicious death do not negatively affect the investigations to be performed in autopsy, so that kidneys and liver may be transplanted appropriately 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Organ nakli, hastalıklar ya da travma nedeniyle işlevini yerine getirmeyen organların yerine canlıdan ya da ölüden alınan organların konulması işlemidir (1)(2)(3). Günümüzde pek çok organ ve dokunun nakli gerçekleştirilebilmektedir (2,4).…”
Section: Introductionunclassified